Molecular and Morphological Characteristics of Redigobius tambu-jon Collected from Tuweley River, Tolitoli, Central Sulawesi, Indonesia - Laheng, Suardi; Putri, Dwi Utami; Putri, Ika Wahyuni; Aliyas; Paisal, Moh. (Journal of Aquaculture and Fish Health, 2025)
The Tuweley River is an aquatic ecosystem rich in biodiversity. One of the fish species found in this river is Redigobius. Studies on this species' molecular and morphological aspects are very important to support conservation efforts and management of local aquatic resources. This research was conducted from September 2022 to March 2023. The specimen collection is in the Tuweley River, Tolitoli Regency, Central Sulawesi Province, Indonesia. Morphological character measurements were carried out at the Integrated Laboratory of Universitas Madako Tolitoli, while DNA (Deoxyribonucleic Acid) analysis was carried out at the Bionesia Laboratory, Bali. This study employs a quantitative descriptive approach to analyze the data. The data examined include morphological and molecular characteristics (qualitative) and quantitative data consisting of morphometric, meristic characters, and DNA analysis of R. tambujon. These data were tabulated in table form and analyzed descriptively to obtain a comprehensive overview of the species' characteristics. The study results showed that the fish collected in the Tuweley River were the R. tambujon species, based on DNA analysis and morphological character measurements.